2015
DOI: 10.1016/j.celrep.2015.03.019
|View full text |Cite
|
Sign up to set email alerts
|

E4F1 Is a Master Regulator of CHK1-Mediated Functions

Abstract: It has been previously shown that the polycomb protein BMI1 and E4F1 interact physically and genetically in the hematopoietic system. Here, we report that E4f1 is essential for hematopoietic cell function and survival. E4f1 deletion induces acute bone marrow failure characterized by apoptosis of progenitors while stem cells are preserved. E4f1-deficient cells accumulate DNA damage and show defects in progression through S phase and mitosis, revealing a role for E4F1 in cell-cycle progression and genome integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 37 publications
4
25
0
Order By: Relevance
“…Additionally, the senescence-promoting effect of apelinergic suppression was not cell-specific as incubation of human cardiac fibroblasts (HCFs) with aplnr antagonist (ML221) also upregulated cellular p21 (Figure 3I) and increased SA-β-gal staining (Figure 3H and S2I). As apln-aplnr interaction on endothelial surface lowers cAMP (Mclean et al, 2012), we measured activities of 20 cAMP-dependent transcription factors (TF) and observed that apln Kd increases activity of senescence-promoting Sp1 (Wu et al, 2007) and decreases activity of proliferation-promoting E4F (Grote et al, 2015) and GATA4 (Figure 3J). Dysregulation of these TFs, either individually or in unison, likely contributes to cellular senescence seen after the genetic or pharmacological suppression of apln signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the senescence-promoting effect of apelinergic suppression was not cell-specific as incubation of human cardiac fibroblasts (HCFs) with aplnr antagonist (ML221) also upregulated cellular p21 (Figure 3I) and increased SA-β-gal staining (Figure 3H and S2I). As apln-aplnr interaction on endothelial surface lowers cAMP (Mclean et al, 2012), we measured activities of 20 cAMP-dependent transcription factors (TF) and observed that apln Kd increases activity of senescence-promoting Sp1 (Wu et al, 2007) and decreases activity of proliferation-promoting E4F (Grote et al, 2015) and GATA4 (Figure 3J). Dysregulation of these TFs, either individually or in unison, likely contributes to cellular senescence seen after the genetic or pharmacological suppression of apln signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Initially identified as a cellular target of the E1A viral oncoprotein (16), E4F1 was then described as a physical interactor of several tumor suppressors that gate cell division and survival in proliferating cells, including pRB, RASSF1A, p14 ARF , and p53 (17)(18)(19)(20)(21). E4F1 is essential for early embryonic mouse development (22), and for either proliferation or survival of actively dividing mammalian cells (23)(24)(25). In proliferating cells, we have recently shown that E4F1 controls genes implicated in cell-cycle checkpoints and genome surveillance, but also unexpectedly, a transcriptional program involved in mitochondria functions (24,26).…”
Section: (E4f1)mentioning
confidence: 99%
“…Besides the function of transcription factors, E4F1 can also act as ubiquitin ligase, including p53 tumor suppressor . Inactivation of E4F1 in mouse and human HS cell lines resulted in an increase in mitochondrial defects and ROS . A pioneer study suggests that E4F1 inactivation delays tumor progression in a hematopoietic‐specific tumor‐prone mouse model and the mice with total body knockout of E4F1 had mitotic defects, chromosomal maladjustment, apoptosis, and embryo death during the peri‐implantation period …”
Section: Introductionmentioning
confidence: 60%
“…Early research suggests that short hairpin RNA (shRNA)‐mediated E4F1 deletion induces mitochondrial defects and ROS‐mediated death has found in myeloid leukemia cell lines …”
Section: Introductionmentioning
confidence: 99%